Parametric Optimization of Solvent Extraction of Soybean Oil - Ismail Abubakar Jumare; Omuya Raheem Momoh; Sani Abubakar Jumare (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Edible oil extraction via favorable conditions is central to industrial growth and sustainability. This paper investigates the optimum conditions for the soybean oil extraction via solid-liquid or leaching mechanism. This was done by varying parameters viz. the solvent concentration, temperature, and time of extraction using a soxhlet apparatus in a water bath. The oil characterization was also carried out focusing on some physic-chemical properties. Statistical analysis was lastly carried out on different parameters of the oil extraction in view of correlation or statistical significance test using Analysis of Variance (ANOVA). Results showed the highest percentage yield of the oil as 19.25 wt. % with the optimum conditions being 180 minutes of extraction, 70 oC, and 300 mL n-hexane. The statistical significance evaluation showed F values of 6545.26, 63.07, 272.65, and 38.75 for soy cake weight loss with corresponding moisture content, variations in solvent extraction, temperature and time with their corresponding oil yields respectively, all greater than their critical F values. However, the F value determined for the sets of oil yield for the 3 parametric variations being 1.21, was found to be less than its critical F value. Hence, these conditions are useful in maximizing soybean oil production at best possible cost. Also, the statistically significant evidence exists from the robust data analysis to show clear relationship on all the tested parametric variations for the oil extraction with their corresponding oil yields. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).